Effect of Aluminum Dust Particles on Plasma Parameters at Different Gas Pressure with Different Dust Contents - Abdulghani, Shahad Emaduldeen; Adnan, Qusay Abbas; Ali, Omar Abdulsada (Iraqi Journal of Science, 2025)
In this work, the effect of aluminum (Al) dust particles on the DC discharge plasma properties in argon was investigated. A magnetron is placed behind the cathode at different pressures and with varying amounts of Al. The plasma temperature (Te) and density (ne) were calculated using the Boltzmann equation and Stark broadening phenomena, which are considered the most important plasma variables through which the other plasma parameters were calculated. The measurements showed that the emission intensity decreases with increasing pressure from 0.06 to 0.4 Torr, and it slightly decreases with the addition of the NPs. The calculations showed that the ne increased and Te decreased with pressure. Both Te and ne were reduced by increasing the content of aluminum dust.